1977
DOI: 10.1111/j.1834-7819.1977.tb05119.x
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐face osteotomy in the adolescent cleft palate patient*

Abstract: Abstract— Retrognathia or retrusion of the maxilla and mid‐face is present in about one‐third of treated cleft palate patients.Surgical repositioning of either the dental segments, or the entire mid‐face into a forward position, can greatly enhance appearance and at the same time provide for a more functional occlusion.Some surgical aspects of this work are presented together with an evaluation of soft tissue change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Peterka et al reported that the deciduous and permanent lateral incisors in the maxillary quadrant with cleft showed the greatest retardation [39]. He also noted delayed eruption of the canine, first and second premolars in the maxillary quadrant with cleft.…”
Section: Delayed Dental Eruptionmentioning
confidence: 98%
See 1 more Smart Citation
“…Peterka et al reported that the deciduous and permanent lateral incisors in the maxillary quadrant with cleft showed the greatest retardation [39]. He also noted delayed eruption of the canine, first and second premolars in the maxillary quadrant with cleft.…”
Section: Delayed Dental Eruptionmentioning
confidence: 98%
“…The effects of surgical cleft repair could result in damage to the tooth bud, or fibrosis and reduced blood supply to the cleft area [18]. Other etiological factors include lack of space in the cleft area [39] and growth attenuation due to improper nutrition as a result of feeding problems [18].…”
Section: Aetiology Of Asymmetric Tooth Formation and Eruptionmentioning
confidence: 99%
“…Due to the prevalence of maxillary osteotomy complications in UCLP patients [38], confusing and complicated orthognathic surgery techniques were proposed for these patients [39][40][41]. Moreover, as in other aspects of orthognathic surgery, Hugo Obwegeser also provided contributions that could be explained as breakthroughs for skeletally cleft reconstruction [35,[42][43][44].…”
Section: Surgical Approachmentioning
confidence: 99%
“…Incomplete, insufficient definitions were presented by previous studies for surgical techniques used for the purpose of warning BCLP patients about possible complications regarding maxillary osteotomy and achieving reliable osteotomy operations [39,53]. Hugo Obwegeser provided significant contributions which may be considered as milestones about cleft surgery on BCLP patients.…”
Section: Surgical Approachmentioning
confidence: 99%
“…Conventionally it was corrected by orthognathic surgery (advancement LeFort I osteotomy) since 1970s [1]. Very often extreme maxillary deficiency is difficult to treat with ALO, as greater advancement was required in such cases [2][3][4][5][6][7][8][9]. The surgical difficulty in ALO includes intra operative hemorrhage, palate exposure leading to sinusitis, scarring from cleft lip palate repair, the less predictable vascular supply, the extend of advancement, the fixation of transposed segments, requirement for bone graft, negative effect on velopharyngeal closure, high risk of bone necrosis and higher post-surgical relapse rates ranging up to 50 % [6,7,9,10].…”
Section: Introductionmentioning
confidence: 99%